Penerapan Sistem Filsafat Pancasila terhadap Kehidupan Mahasiswa Prodi Teknik Industri Universitas PGRI Adi Buana Surabaya - Nur Qidam Aliyanto; Ridho Sampurno; Hustin Nasrul; Jamiatul Hasanah; Alorinda Zantia Mauliba; Arjuna Bekti Laksono; Tiwi Purnawati; Firdaus Rahman; Wagino Wagino; Putri Ayu; Aji Putra; Nabila Maret’atus; Suyono Suyono (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This study investigates how the Pancasila philosophy is applied in the lives of students in the Industrial Engineering Study Program at PGRI Adi Buana University, Surabaya. Data was collected through interviews with Industrial Engineering Study Program students to gain a complete understanding. This research was conducted using a qualitative descriptive approach and phenomenological methodology. This research found that the application of Pancasila values in students' lives had a positive impact on the development of their character, ethics and national spirit. In addition, this research found that collective efforts from various parties can strengthen the internalization of these values, even though there are obstacles in implementing these values. Recommendations include increasing Pancasila-based character education programs and collaboration between universities and related institutions to increase the implementation of Pancasila values.